2011
DOI: 10.4049/jimmunol.1003919
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Promotes Differentiation of Human Cord Blood Fetal T Cells into T Regulatory Cells but Suppresses Their Differentiation into Th17 Cells

Abstract: Progesterone, a key female sex hormone with pleiotropic functions in maintenance of pregnancy, has profound effects on regulation of immune responses. We report here a novel function of progesterone in regulation of naïve cord blood (CB) fetal T cell differentiation into key regulatory T cell subsets. Progesterone drives allogeneic activation-induced differentiation of CB naive, but not adult peripheral blood (PB), T cells into immune suppressive T regulatory cells (Tregs), many of which express FoxP3. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 58 publications
1
144
3
Order By: Relevance
“…Depletion of Tregs results in fetal loss (23). Pregnancy-related hormonal signals, including estrogens and progesterone (1,24,25), appear to support Treg proportion and function, although their exact mode of action remains incompletely understood.…”
mentioning
confidence: 99%
“…Depletion of Tregs results in fetal loss (23). Pregnancy-related hormonal signals, including estrogens and progesterone (1,24,25), appear to support Treg proportion and function, although their exact mode of action remains incompletely understood.…”
mentioning
confidence: 99%
“…In these studies, physiological doses of progesterone were shown to significantly increase the population of Treg cells (Lee et al, 2011;Mao et al, 2010). However, in contrast to these data, Mjosberg et al showed using an in vitro model, that progesterone reduced the Treg cell population in PBMC from nonpregnant women (Mjosberg et al, 2009).…”
Section: Progesteronementioning
confidence: 71%
“…A major mechanism to suppress the T-cell response during pregnancy is mediated by P4. P4 effectively suppresses the generation of T cells producing IFNg (Th1 cells) or IL-17 (Th17 cells) (Piccinni et al, 1995;Miyaura and Iwata, 2002;Lee et al, 2011Lee et al, , 2012. In females, P4 is produced by the corpus luteum of the ovaries after ovulation and in the placenta during pregnancy.…”
Section: P4 Is a Primary Suppressor Of T Cells During Pregnancymentioning
confidence: 99%
“…T cells are regulated at relatively high P4 concentrations (e.g., greater than a few hundred nanograms per milliliter). This level of P4 can effectively suppress the generation of Th1 and Th17 cells (Lee et al, 2011. At the expense of the effector T cells, P4 induces a subset of T cells called ''regulatory T cells.''…”
Section: P4 Is a Primary Suppressor Of T Cells During Pregnancymentioning
confidence: 99%